Sensory attributes and volatile composition of a dry white wine under different packing configurations - Moreira, N. (2018)
The aim of this work was to study the effect of different configurations of packaging on the volatile composition and sensory properties of a white wine. Certain oenological parameters were also evaluated. Bag-in-box (BIB) and glass bottles sealed with two different cork stoppers, natural and Neutrocork (technical), were used in the experiments. Analysis were carried out before packaging and after 3, 6 and 12 months of storage. Results showed that wines packaged in BIB presented higher levels of brown color than wines in bottles sealed with corks. In all packaging configurations, the content of free SO2 decreased with storage time; however, BIB wines showed a lower content of free SO2 than bottle wines during 12 months. Moreover, wines under BIB presented a significant lower amount of 2-phenylethanol, 2-phenylethyl acetate, isoamyl acetate, ethyl butanoate, ethyl hexanoate, ethyl octanoate, linalool and b-damascenone than bottled wines.